2012
DOI: 10.1063/1.4729929
|View full text |Cite
|
Sign up to set email alerts
|

Single GaInP nanowire p-i-n junctions near the direct to indirect bandgap crossover point

Abstract: Axially defined GaInP single nanowire (NW) p-i-n junctions are demonstrated, with photocurrent response and yellow-green electroluminescence near the indirect bandgap crossover point at 2.18 eV (569 nm). We use DEZn and H2S as p- and n-type dopants, and find that they both affect the material composition and the crystal structure. The photovoltaic efficiency is comparable to single NW devices from binary III-V materials. These results demonstrate the potential of GaInP nanowires as a high-bandgap material for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Of course, other ternary alloys may be of interest for multi‐junction cells. The growth of some of these ternary compound semiconductor nanowires, most notably InGaP, AlGaAs and GaAsP, has already been demonstrated on Si or other substrates 175–181. As discussed previously, the lattice mismatch between the nanowires and Si is not a concern provided the nanowire–substrate contact area is below the critical diameter for dislocations.…”
Section: Design For High Efficiency Pvmentioning
confidence: 88%
See 1 more Smart Citation
“…Of course, other ternary alloys may be of interest for multi‐junction cells. The growth of some of these ternary compound semiconductor nanowires, most notably InGaP, AlGaAs and GaAsP, has already been demonstrated on Si or other substrates 175–181. As discussed previously, the lattice mismatch between the nanowires and Si is not a concern provided the nanowire–substrate contact area is below the critical diameter for dislocations.…”
Section: Design For High Efficiency Pvmentioning
confidence: 88%
“…Recently, another model was proposed whereby dopants cause nucleation‐limited growth 163. Finally, doping can affect the composition of ternary III–V alloys 164. A review on nanowire doping is provided in Ref.…”
Section: Dopingmentioning
confidence: 99%
“…112 Most interestingly, doping may also modify the compositions for ternary semiconductor NW. Wallentin et al 113 reported the growth of GaxIn(1-x)P NWs with p-i-n radial junction. They found that the S doped region is slightly more In rich (x=0.7)…”
Section: And the Elimination Ofmentioning
confidence: 99%
“…It has been shown that the (Ga,In)P exhibits a direct-indirect band gap crossover which depends on the In fraction [7][8][9][10]. It is a material largely used in optical applications such as light-emitting devices, solar cells and heterojunction structures [11,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…The MOCVD is a common technique to grow (Ga,In)P nanowires, it is usually a seed assisted growth process [8,11,14,15]. The traditional MOCVD method uses organometallic compounds as precursor source of the elements.…”
Section: Introductionmentioning
confidence: 99%